The Poetics of Speech in the Medieval Spanish Epic - Bailey, Matthew, 1955- (Book collections on Project MUSE., 2010)
In Latin and other vernacular texts from the same period, authors identify their sources as oral, describe oral compositional techniques, and detail modes of processing texts in medieval monastic environments. Using the information provided by these details, as well as a close technical reading of the three epic poems, Bailey incorporates the methodologies and concepts of discourse analysis in an examination of expression in the Spanish epic and points convincingly to oral composition as the initial step in text creation for the period."--Pub. desc.